2004
DOI: 10.1093/jhered/esh029
|View full text |Cite
|
Sign up to set email alerts
|

Male-biased Mutation Rates and the Overestimation of Extrapair Paternity: Problem, Solution, and Illustration Using Thick-Billed Murres (Uria lomvia, Alcidae)

Abstract: The widespread utility of hypervariable loci in genetic studies derives from the high mutation rate, and thus the high polymorphism, of these loci. Recent evidence suggests that mutation rates can be extremely high and may be male biased (occurring in the male germ-line). These two factors combined may result in erroneous overestimates of extrapair paternity, since legitimate offspring with novel alleles will have more mismatches with respect to the biological father than the biological mother. As mutations ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(33 citation statements)
references
References 48 publications
1
31
0
Order By: Relevance
“…The addition of this fifth species of the auk family did not affect our earlier finding (Anker-Nilssen et al 2008b) that no significant inter-specific variation in the rate of EPP, as measured by the proportion of extra-pair nestlings, can be found within the Alcidae. Among the 270 family units of auks studied so far, however, only ten factual cases (3.8%) of EPP have been documented (Anker-Nilssen et al 2008b and this study;Birkhead et al 2001;Ibarguchi et al 2004;Lifjeld et al 2005, accounting also for the results of Wojczulanis-Jakubas et al 2009).…”
Section: Resultsmentioning
confidence: 51%
See 1 more Smart Citation
“…The addition of this fifth species of the auk family did not affect our earlier finding (Anker-Nilssen et al 2008b) that no significant inter-specific variation in the rate of EPP, as measured by the proportion of extra-pair nestlings, can be found within the Alcidae. Among the 270 family units of auks studied so far, however, only ten factual cases (3.8%) of EPP have been documented (Anker-Nilssen et al 2008b and this study;Birkhead et al 2001;Ibarguchi et al 2004;Lifjeld et al 2005, accounting also for the results of Wojczulanis-Jakubas et al 2009).…”
Section: Resultsmentioning
confidence: 51%
“…Although the underlying mechanisms are often difficult to explain, much of the variation in EPP rates is also linked to taxonomic family or order level (Arnold and Owens 2002). For members of the auk family (Alcidae), studies of EPP have been published for four of the six Atlantic species, all of which demonstrated low or no EPP: estimated at 7.8% (95% confidence interval, CI, recalculated at 2.3-19.3%, n = 77 offspring) in the Common Guillemot Uria aalge (Birkhead et al 2001), at 7.4% (95% CI calculated at 0.9-24.3%, n = 27 offspring) in Brünnich's Guillemot Uria lomvia (Ibarguchi et al 2004), and at 3.1% (95% CI = 0.39-10.44%, n = 64 offspring) in the Little Auk Alle alle (Wojczulanis-Jakubas et al 2009), whereas no incidence of EPP was found in studies of the Little Auk (95% CI = 0-10.9%, n = 26 offspring, Lifjeld et al 2005) and the Atlantic Puffin Fratercula arctica (95% CI = 0-7.6%, n = 38 offspring, Anker-Nilssen et al 2008b).…”
Section: Introductionmentioning
confidence: 99%
“…Cumulative probabilities of resemblance (P Rcum ; Ibarguchi et al 2004) were calculated for these three chicks, excluding loci with the mismatched alleles. In two cases, the probabilities of sharing alleles by chance were so high (0.2 9 10 -3 and 1.3 9 10 -3 , respectively) that mismatches due to mutation could be ruled out.…”
Section: Resultsmentioning
confidence: 99%
“…3.0.3 software (Kalinowski et al 2007) ( Table 1). Allele frequencies were used to calculate the cumulative probability of resemblance (P RCum ) for specific parent-offspring cases where ambiguous mismatches occurred (Ibarguchi et al 2004).…”
Section: Parentage Analysesmentioning
confidence: 99%
“…In those cases where a mismatching locus was observed, we calculated the cumulative resemblance probability (P RCum ). This method allows discrimination between the possibilities of true parentage or sharing alleles by chance, based on the population frequencies of the alleles shared by two individuals (Ibarguchi et al 2004). We calculated EPP and IBP 95% confidence intervals based on the binomial distribution according to Sokal and Rohlf (2009).…”
Section: Parentage Analysismentioning
confidence: 99%